2010
DOI: 10.1007/s12043-010-0006-y
|View full text |Cite
|
Sign up to set email alerts
|

Potential energy curves for neutral and multiply charged carbon monoxide

Abstract: Potential energy curves of various electronic states of CO n+ (0 ≤ n ≤ 6) are generated at MRCI/CASSCF level using cc-pvQZ basis set and the results are compared with available experimental and theoretical data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 22 publications
(32 reference statements)
3
17
0
Order By: Relevance
“…We obtained an equilibrium distance of 2.357 a.u., in agreement with the values of Ref. 80. The rovibrational energies and wave functions were obtained by solving the radial Schrödinger equation using a B-spline method.…”
Section: Designationsupporting
confidence: 80%
See 1 more Smart Citation
“…We obtained an equilibrium distance of 2.357 a.u., in agreement with the values of Ref. 80. The rovibrational energies and wave functions were obtained by solving the radial Schrödinger equation using a B-spline method.…”
Section: Designationsupporting
confidence: 80%
“…74 The ground X 3 Π state of CO 2+ has been described in several previous studies. 17,20,[75][76][77][78][79][80] These studies provide equilibrium distance values between 2.23 a.u. and 2.46 a.u., which serves to illustrate the difficulty of accurate electronic structure calculations on dications.…”
Section: Molecular Datamentioning
confidence: 99%
“…These KER values are smaller than the KER values calculated from the CE model. Different electronic states of the CO 3+ molecular ion, the calculated KER values, and the dissociation limits for both channels are listed in Table VI (taken from [32,43]). For both channels, the theoretically calculated KER values show a reasonably good agreement with our observed KER values.…”
Section: Fragmentation Of Co 3+mentioning
confidence: 99%
“…The KERD for the channel C 3+ + O + is not shown due to its low statistics; however, it is found that it has a distribution between 7 eV and 35 eV. The molecular states of the CO 4+ ion, their associated KER, and the dissociation limits for different molecular states are listed in Table VII (the value of KER and the dissociation limit are calculated using the values taken from [5,6,43]). It is obvious from Table VII that the calculated KER values explain the KERD; the high-energy side of KERD may be arising either from higher states of the CO 4+ molecular ion or from the lower dissociation limits.…”
Section: Fragmentation Of Co 4+mentioning
confidence: 99%
See 1 more Smart Citation